Improving Gross Motor Skills Through Playing Jump Rope in Early Childhood at Ar Rahma Kindergarten - Mahmudah, Elis; Kurniawaty, Lia; Yuntina, Lily (LPPM Universitas Pahlawan Tuanku Tambusai, Riau, Indonesia, 2024)
Gross motor skills involve body movements that are important for early childhood development. Early childhood education institutions play a role in providing services that suit children's needs. Research on gross motor skills was conducted on children aged 5-6 years at ARRAHMA, focusing on the jumping rope game activity. The research method used is classroom action research. This research involved two cycles and 10 meetings with 10 children. Data was collected through interviews and observations. The research results show that jumping rope activities can improve gross motor skills, as evidenced by the percentage increase in each cycle. In cycle I, there was an increase of 10%, while in cycle II, there was excellent development of 80%. Based on these results, it can be concluded that the rope jumping activity effectively improves gross motor skills in children aged 5-6 years at ARRAHMA.